2016
DOI: 10.1002/nau.23142
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor release from the urothelium increases via activation of bladder C‐fiber in rats with cerebral infarction

Abstract: Results indicate that expression of sensor molecules in the bladder is altered by distant infarction in the brain. ATP and NGF release from the urothelium also increased. NGF release was related to activation of bladder C-fibers. Bladder C-fibers might not contribute much to decreased bladder capacity caused by cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…KPR-5714 dose-dependently increased the mean voided volume and decreased voiding frequency without affecting total voided volume (Table 2). Yokokawa et al (2017) revealed that bladder C-fibers are activated by cerebral infarction, and C-fiber afferent nerves play an important role on the secretion of nerve growth factor; thus, we supposed that the improvement of the voiding behavior by KPR-5714 may be also mediated via inhibition of bladder C-fiber hyperactivity similar to the case of acetic acid instillation.…”
Section: Discussionmentioning
confidence: 83%
“…KPR-5714 dose-dependently increased the mean voided volume and decreased voiding frequency without affecting total voided volume (Table 2). Yokokawa et al (2017) revealed that bladder C-fibers are activated by cerebral infarction, and C-fiber afferent nerves play an important role on the secretion of nerve growth factor; thus, we supposed that the improvement of the voiding behavior by KPR-5714 may be also mediated via inhibition of bladder C-fiber hyperactivity similar to the case of acetic acid instillation.…”
Section: Discussionmentioning
confidence: 83%
“…NGF is released in the inflammatory status and can modulate the expression of the P2X3 receptor. In addition, activation of the bladder C-fiber owing to various etiologies induces the release of NGF from the urothelium [40]. The findings of the current study suggested that NGF and associated purinergic signaling molecules were involved in BPAO-induced bladder overactivity.…”
Section: Discussionmentioning
confidence: 53%
“…Nerve growth factor (NGF) is a protein primarily responsible for the differentiation and survival of neurons in the peripheral nervous system [ 4 ], so NGF has been one of neuroprotective agents for treating cerebral infarction [ 5 – 7 ] and ischemic brain [ 8 , 9 ]. The situation of focus recovery was observed and evaluated after cerebral infarction treated by NGF and other neuroprotective agents, which needed more reliable objective indicators.…”
Section: Introductionmentioning
confidence: 99%